Morphological integration in the hominid midfoot. Issue 170 (September 2022) - Komza, Klara; Viola, Bence; Netten, Teagan; Schroeder, Lauren
Abstract: The calculation of morphological integration across living apes and humans may provide important insights into the potential influence of integration on evolutionary trajectories in the hominid lineage. Here, we quantify magnitudes of morphological integration among and within elements of the midfoot in great apes and humans to examine the link between locomotor differences and trait covariance. We test the hypothesis that the medial elements of the great ape foot are less morphologically integrated with one another compared to humans based on their abducted halluces, and aim to determine how adaptations for midfoot mobility/stiffness and locomotor specialization influence magnitudes of morphological integration. The study sample is composed of all cuneiforms, the navicular, the cuboid, and metatarsals 1–5 of Homo sapiens ( n  = 80), Pan troglodytes ( n  = 63), Gorilla gorilla ( n  = 39), and Pongo sp. ( n  = 41). Morphological integration was quantified using the integration coefficient of variation of interlandmark distances organized into sets of a priori-defined modules. Magnitudes of integration across these modules were then compared against sets of random traits from the whole midfoot. Results show that all nonhuman apes have less integrated medial elements, whereas humans have highly integrated medial elements, suggesting a link between hallucal abduction and reduced levels of morphological integration. However, we find considerable variation in magnitudes of morphological integration across metatarsals 2–5, the intermediate and lateral cuneiform, the cuboid, and navicular, emphasizing the influence of functional and nonfunctional factors in magnitudes of integration. Lastly, we find that humans and orangutans show the lowest overall magnitudes of integration in the midfoot, which may be related to their highly specialized functions, and suggest a link between strong diversifying selection and reduced magnitudes of morphological integration.